The Influence of Good Corporate Governance, Earning Power and Leverage on Earnings Management in Manufacturing Companies in the Industrial and Consumer Goods Sector: Pengaruh Good Corporate Governance, Earning Power dan Leverage Terhadap Manajemen Laba pada Perusahaan Manufaktur Sektor Industri dan Barang Konsumsi - Firman, Karinda; Widodo, Heri (Indonesian Journal of Law and Economics Review, 2022)
Earnings management becomes a special day for organizations because there are often conflicts of interest called information asymmetry. The purpose of this research is to know whether the variables of GCG, earning power and leverage have an influence on the earnings management variable. The population in this research is the industrial sector companies and manufactured consumer goods on the IDX in 2017 to 2019. Purposive sampling is a sampling technique taken to determine the sample in this research so that this study found a sample of 15 companies so that the total samples taken for 3 years from 15 companies are 45 companies then secondary data which is the source of data in this study is tabulated and processed with the help of SPSS version 25 then a set of test tools to support the hypothesis with a partial t-test. This is done is the size of the Board of Commissioners which is a proxy for GCG proven to be able to influence earnings management. Managerial ownership which is a proxy for GCG is proven to be able to influence earnings management. Institutional ownership which is a proxy for GCG is able to influence earnings management. The size of the Audit Committee, which is a proxy for GCG, is proven to be able to influence earnings management. Earning Power is proven to be able to influence earnings management. Leverage is proven to be able to influence earnings management.